2021
DOI: 10.1002/cam4.4457
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and relative risk of metachronous second primary cancers for 16 cancer sites, Osaka, Japan, 2000–2015: Population‐based analysis

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 34 publications
2
36
1
Order By: Relevance
“…The reported SIRs ranged from 0.84 (3) to 1.84 (24). All but ve (3,7,19,21,24) estimated SIRs ranging between 1.00 and 1.50.…”
Section: Results Of Literature Searchmentioning
confidence: 98%
See 4 more Smart Citations
“…The reported SIRs ranged from 0.84 (3) to 1.84 (24). All but ve (3,7,19,21,24) estimated SIRs ranging between 1.00 and 1.50.…”
Section: Results Of Literature Searchmentioning
confidence: 98%
“…Larger studies comparing SPC counts observed under these two common sets of guidelines would help clarify this issue. However, even if SPC coding discrepancies do account for the majority of the heterogeneity contributed by Diab et al, this would not explain the rest of the heterogeneity, which remained signi cant even following the elimination of four further studies identi ed as major drivers of heterogeneity (7,11,20,24). It is likely that including studies from three different continents contributed to heterogeneity, since SPC risks in these continents were found to vary signi cantly.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations